SWOT Analysis Using IFAS and EFAS Methods to Shorten Waiting Times for Pharmaceutical Services at Hospital X, Pekanbaru City - Nailul Fithri Arrasily; Herniwanti Herniwanti (Jurnal Multidisiplin Sahombu, 2026)
This study aimed to analyze strategies for improving outpatient pharmacy service waiting time at RS Mesra using a SWOT analysis approach. A qualitative research design was applied by identifying internal and external factors that influence pharmacy service performance. Data were collected through in-depth interviews, observations, and SWOT questionnaires involving the head of the pharmacy unit, pharmacists, pharmacy technicians, and hospital management selected through purposive sampling. Internal and external factors were analyzed using the Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) matrices. The IFAS results showed that weaknesses outweighed strengths, indicating internal challenges such as limited human resources, long compounding processes, and high patient queues. Meanwhile, the EFAS results revealed that opportunities were greater than threats, highlighting favorable external conditions including national waiting time standards, technological advancements, and managerial support. The SWOT matrix positioned the outpatient pharmacy unit in a condition that requires both improvement and development strategies. Therefore, optimizing internal resources, strengthening information systems, and utilizing external opportunities are essential to reduce waiting time and enhance the quality of pharmacy services in a patient-centered hospital setting.